Contribution of segmental kinetic energy to forward propulsion of the centre of mass: analysis of sprint acceleration - Slawinski, J.; Houel, N.; Moreau, C.; Mahlig, A.; Dinu, D. (Journal of Sports Sciences, 2022)
This study aimed to measure the contribution of each body segment to the production of total body kinetic energy (KE) during a 40-m sprint. Nine recreational sprinters performed two 40-m sprints wearing a MVN Biomech suit (Xsens). Data recorded were used to calculate total body KE, and the KE of each segment. The KE of each segment was then expressed as a percentage of the total body KE. We divided the sprint into three phases: 1 - start to maximal power (Pmax), 2 - Pmax to maximal velocity (Vmax), and 3 - Vmax to the end of the 40 m. Total body KE increased from the start to the end of the 40-m sprint (from 331.3 ± 68.4 J in phase 1 to 2378.8 ± 233.0 J in phase 3; p = 0.001). The contribution of the head-trunk increased (from 39.5 ± 2.4% to 46.3 ± 1.1%; p = 0.05). Contribution of the upper and lower limbs decreased over the three phases (respectively from 15.7 ± 2.5% to 10.6 ± 0.6% and from 44.8 ± 2.1% to 43.1 ± 1.5%; p = 0.05). This study revealed the important contribution of the trunk to forward propulsion throughout the entire acceleration phase.